2003
DOI: 10.3998/ark.5550190.0004.a47
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study of the hydrolysis of nitrocefin mediated by B.cereus metallo-β-lactamase

Abstract: The hydrolysis of the β-lactam compound nitrocefin by the metallo-β-lactamase from B.cereus (BcII) was studied by pre-steady state kinetics measurements, followed by absorbance, fluorescence and diode array detection. In contrast with the results reported for the homologous enzymes CcrA from B.fragilis and L1 from S.maltophilia, no accumulation of an anionic intermediate could be evidenced. The rationale for this observation can be tracked on the lower binding affinity toward a second Zn(II) ion in this enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 17 publications
4
22
0
Order By: Relevance
“…Behavior varies widely across the B1 MBL subclass, as summarized in Table 5 . 24 27 , 48 , 49 , 55 , 57 60 To support this, we include two reports on CcrA here. One is based on an early study by Benkovic and co-workers that reported an optical titration consistent with distributed Co(II) binding.…”
Section: Discussionmentioning
confidence: 99%
“…Behavior varies widely across the B1 MBL subclass, as summarized in Table 5 . 24 27 , 48 , 49 , 55 , 57 60 To support this, we include two reports on CcrA here. One is based on an early study by Benkovic and co-workers that reported an optical titration consistent with distributed Co(II) binding.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to these results, no accumulation of an anionic intermediate could be detected in reactions catalysed by BCII and the rate of substrate depletion and product formation are similar [ 55 ]. However, for the BCII-catalysed hydrolysis under cryoenzymological conditions, a slightly red-shifted intermediate (440 nm) was observed, which was suggested to be a nitrocefin-like tetrahedral intermediate [ 56 ].…”
Section: Metallo β -Lactamasesmentioning
confidence: 91%
“…Based on these observations it was concluded that both the replacement of the arginine residue and the introduction of the second metal-ion are evolutionary tools for accelerating C–N bond fission in MBL catalysed hydrolysis of β -lactams. However, an important role in lowering the energy barrier for breaking the C–N bond must come from other enzyme structural rearrangements, since the reciprocal, that is, the sole replacement of the arginine by a cysteine residue and the insertion of a second zinc-ion in BCII, only marginally (two fold) improves the catalytic activity [ 55 ].…”
Section: Metallo β -Lactamasesmentioning
confidence: 99%
“…The accumulation of the nitrocefin intermediate is different among MBLs: there is barely any intermediate formed with BcII or IMP-1 . Minor perturbations, such as as second sphere mutations that change the hydrogen bond network or loop changes, can lead to large changes in the accumulation of this and other intermediates .…”
Section: Catalytic Mechanism Of Mblsmentioning
confidence: 99%